A method for preparing high-temperature wear-resistant multilayer material on the surface of precision parts
The CoCrFeNi/Ti/CuNb multi-layer material is formed on the surface of precision parts through magnetron sputtering multi-target co-sputtering technology, which solves the problem of poor wear resistance at high temperatures, achieves higher wear resistance and longer service life, and ensures environmental protection.
Patent Information
- Application Number
- CN202510061554.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing surface coatings of precision parts have poor wear resistance at high temperatures, resulting in problems such as loss of accuracy, lubrication failure, contact fatigue, material deterioration, structural deformation and aggravation of vibration.
Magneto-controlled sputtering multi-target cosputtering technology is used to form CoCrFeNi/Ti/CuNb multi-layer material on the surface of precision parts. By cosputtering and alternating sputtering of Ti, CuNb and CoCrFeNi targets, 11 high-temperature wear-resistant film materials were prepared.
It significantly improves the wear resistance of precision parts surfaces at high temperatures, extends service life, enhances reliability, and ensures the purity and environmental protection of the material under a high vacuum environment.
Smart Images

Figure CN119465059B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a high-temperature wear-resistant coating on the surface of a precision part. Background Art
[0002] With the rapid development of my country's manufacturing industry, precision spherical bearings are widely used in key parts such as automobile gearboxes and carrier-based aircraft engines. However, due to their high temperature and high wear service environment, they will cause damage to precision parts, such as loss of accuracy, lubrication failure, contact fatigue, material degradation, structural deformation, increased vibration, etc. Therefore, in order to ensure the use effect of precision parts in high temperature and wear service environment, it is urgent to design a preparation method of high temperature wear-resistant multilayer material to obtain high temperature wear-resistant multilayer material that can be used in the above environment to protect precision parts, thereby solving the problems existing in the above-mentioned prior art, extending its service life and enhancing its reliability. Summary of the invention
[0003] The present invention aims to solve the technical problem that the surface coating of precision parts has poor wear resistance at high temperatures, and provides a method for preparing a high-temperature wear-resistant multilayer material on the surface of precision parts.
[0004] The preparation method of the high temperature wear-resistant multilayer material for the surface of precision parts of the present invention is carried out according to the following steps:
[0005] S1. Grind, polish and ultrasonically clean the working surface of the precision parts in turn to remove impurities, and then fix the precision parts on the motor shaft of the sample stage so that the two can rotate coaxially;
[0006] S2, respectively installing the sample stage, Ti target, CuNb target and CoCrFeNi target in S1 in the sputtering chamber, and then evacuating the sputtering chamber;
[0007] S3, filling the sputtering chamber with argon gas;
[0008] S4, connecting three power supplies to the three targets respectively, adjusting the bias voltage and the sputtering power of the Ti target, the CuNb target and the CoCrFeNi target;
[0009] S5. Sputtering the working surface of precision parts:
[0010] ①. During the sputtering process, keep the sample stage rotating, keep the baffles of the three targets of Ti, CuNb and CoCrFeNi open, and perform three-target co-sputtering for 15min~20min;
[0011] ②. Turn off the CoCrFeNi target, and co-sputter the TiCuNb layer with the Ti and CuNb targets for 15min~20min;
[0012] ③, repeat the above steps ① and ② 4 times in sequence;
[0013] ④. Finally, the three targets of Ti, CuNb and CoCrFeNi were co-sputtered for 15-20 minutes to form the last layer of high entropy film. A total of 11 layers of high-temperature wear-resistant film materials were prepared on the working surface of the precision parts, which were recorded as CoCrFeNi / Ti / CuNb multilayer materials.
[0014] S6. After sputtering, close the target baffle, turn off the power supply and argon valve, and take out the sample.
[0015] Design principle of the present invention:
[0016] 1. The present invention adopts a magnetron sputtering multi-target co-sputtering method to form a laminated composite film on the surface of precision parts such as shafts, and the selected target materials are CoCrFeNi target, Ti target and CuNb target. Among them, Ti is an important metal element with high specific strength, good compatibility, and easy to form compounds with various metals, so that the Ti target plays a role in stabilizing the organizational structure and connecting the target materials of various elements in series during the magnetron sputtering process; Cu is a self-lubricating element, which is easy to form a self-lubricating structure of copper oxide (CuO) or cuprous oxide (Cu2O), and it is easy to form a lubricating phase with excellent wear resistance with elements such as Ni and Ti, reducing severe adhesion during friction; Nb is a high-temperature resistant element, which is easy to form stable metal compounds with metal elements such as CoCrFeNiTi, is not easy to change at high temperatures, and significantly improves the high-temperature performance of the film;
[0017] 2. In the preparation process of the multilayer film of the present invention, due to the presence of a large number of interfaces, these interfaces can effectively hinder the movement of dislocations, and a large number of self-lubricating phases cooperate together to improve the hardness and wear resistance of the material, and the multilayer film structure can optimize the stress distribution of the entire coating by adjusting the thickness ratio and material between each layer. This optimization helps to reduce the cracking or peeling of the coating caused by stress concentration, improve the durability of the coating, and make the multilayer film have better performance than the single-layer film. At the same time, the high entropy film has amorphous characteristics, and the single-element or double-element alloy film has nanocrystalline characteristics. This type of amorphous-coated nanocrystalline structure film has the advantages of more stable structure, high strength and good impact resistance.
[0018] The present invention has the following beneficial effects:
[0019] 1. Compared with the CoCrFeNi / Ti multilayer material (CuNb target is removed and other processes remain unchanged), the CoCrFeNi / Ti / CuNb multilayer material prepared by the present invention has Cu and Nb elements added to the coating. Cu is a self-lubricating element, which is easy to form a self-lubricating structure of a copper oxide (CuO) or cuprous oxide (Cu2O) layer, and is easy to form a lubricating phase with excellent wear resistance with elements such as Ni and Ti, thereby reducing severe adhesion during friction. Nb is a high-temperature resistant element, which is easy to form a stable metal compound with metal elements such as CoCrFeNiTi, significantly improving the high-temperature performance, making the high-temperature wear performance of the CoCrFeNi / Ti / CuNb multilayer material more excellent.
[0020] 2. Compared with the CoCrFeNi / Ti / CuNb single-layer material (three targets are sputtered together), the CoCrFeNi / Ti / CuNb multilayer material prepared by the present invention has a large number of interfaces in the multilayer film, which can effectively hinder the movement of dislocations, thereby improving the hardness and wear resistance of the material, and the multilayer film structure can optimize the stress distribution of the entire coating by adjusting the thickness ratio and material selection between the layers. This optimization helps to reduce the cracking or peeling of the coating caused by stress concentration, improve the durability of the coating, and make the high-temperature wear performance of the CoCrFeNi / Ti / CuNb multilayer material more excellent;
[0021] 3. The present invention utilizes a sample stage rotating device to achieve uniform coating on the substrate surface to achieve conformal processing. This technology is particularly suitable for the preparation of coatings on complex shapes or curved surfaces. At the same time, the coating deposition process can be precisely controlled to achieve perfect coverage of complex shapes and ensure uniformity of the coating on complex shapes or curved surfaces.
[0022] 4. The high-temperature wear-resistant multilayer material prepared by the present invention is prepared under a high vacuum environment, avoiding interference from impurities in the air, thereby ensuring the purity of the material, and does not generate pollutants such as waste residue and waste gas. It is an environmentally friendly method for preparing high-temperature wear-resistant multilayer materials on the surface of precision parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the CoCrFeNi / Ti / CuNb multilayer material prepared in Experiment 1;
[0024] Figure 2 SEM image of CoCrFeNi / Ti / CuNb multilayer material prepared in experiment 1;
[0025] Figure 3 This is a real photo of the precision spherical plain bearing 42CrMo steel used in Experiment 1;
[0026] Figure 4This is a comparison chart of tribological curves. DETAILED DESCRIPTION
[0027] Specific implementation method 1: This implementation method is a method for preparing a high-temperature wear-resistant multilayer material on the surface of a precision part, which is specifically carried out in the following steps:
[0028] S1. Grind, polish and ultrasonically clean the working surface of the precision parts in turn to remove impurities, and then fix the precision parts on the motor shaft of the sample stage so that the two can rotate coaxially;
[0029] S2, respectively installing the sample stage, Ti target, CuNb target and CoCrFeNi target in S1 in the sputtering chamber, and then evacuating the sputtering chamber;
[0030] S3, filling the sputtering chamber with argon gas;
[0031] S4, connecting three power supplies to the three targets respectively, adjusting the bias voltage and the sputtering power of the Ti target, the CuNb target and the CoCrFeNi target;
[0032] S5. Sputtering the working surface of precision parts:
[0033] ①. During the sputtering process, keep the sample stage rotating, keep the baffles of the three targets of Ti, CuNb and CoCrFeNi open, and perform three-target co-sputtering for 15min~20min;
[0034] ②. Turn off the CoCrFeNi target, and co-sputter the TiCuNb layer with the Ti and CuNb targets for 15min~20min;
[0035] ③, repeat the above steps ① and ② 4 times in sequence;
[0036] ④. Finally, the three targets of Ti, CuNb and CoCrFeNi were co-sputtered for 15-20 minutes to form the last layer of high entropy film. A total of 11 layers of high-temperature wear-resistant film materials were prepared on the working surface of the precision parts, which were recorded as CoCrFeNi / Ti / CuNb multilayer materials.
[0037] S6. After sputtering, close the target baffle, turn off the power supply and argon valve, and take out the sample.
[0038] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the precision part described in S1 is a shaft structure. The rest is the same as the specific implementation method 1.
[0039] Specific implementation method 3: This implementation method is different from the specific implementation method 2 in that the shaft structure described in S1 is a spherical bearing, a gear or a lead screw. The rest is the same as the specific implementation method 2.
[0040] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the ultrasonic cleaning described in S1 is ultrasonic cleaning in anhydrous ethanol for 5 min to 10 min, the ultrasonic frequency is 60 Hz to 90 Hz, and then blow-drying with cold air. Others are the same as specific embodiments 1 to 3.
[0041] Specific implementation example 5: This implementation example is different from specific implementation example 4 in that the flow rate of the argon gas in S3 is 30 sccm to 50 sccm. The rest is the same as specific implementation example 4.
[0042] Specific implementation example 6: This implementation example is different from the specific implementation example 5 in that the three power sources described in S4 are all DC power sources. The rest is the same as the specific implementation example 5.
[0043] Specific embodiment 7: This embodiment differs from specific embodiment 6 in that: in S4, the sputtering power of the Ti target and the CuNb target is adjusted to 100 W, the sputtering power of the CoCrFeNi target is 150 W, and the bias voltage is -80 V. Other aspects are the same as specific embodiment 6.
[0044] The present invention is verified by the following tests:
[0045] Experiment 1: This experiment is a method for preparing a high-temperature wear-resistant multilayer material on the surface of a precision part. The coating is prepared using a vacuum three-target magnetron sputtering coating machine. The coating substrates are single-polished silicon wafers and precision spherical bearing 42CrMo steel. The coating samples on the single-polished silicon wafer substrate are used to characterize the friction coefficient, while the coating samples on the precision spherical bearing 42CrMo steel are used for SEM testing. The specific steps are as follows:
[0046] S1. For the inner ring working surface of the precision spherical plain bearing 42CrMo steel (such as Figure 3 ) Use 400, 800, 1200, 1500, 2000 grit sandpaper to grind in sequence, and then polish to make the surface mirror-like; then put the precision spherical bearing 42CrMo steel and the single-polished silicon wafer together in anhydrous ethanol for ultrasonic cleaning for 10 minutes, the ultrasonic frequency is 70Hz, and then blow dry with cold air, and then fix the two substrates together on the motor shaft of the sample stage so that the two can rotate coaxially;
[0047] S2, install the sample stage, Ti target, CuNb target and CoCrFeNi target in S1 in the sputtering chamber, and then use a mechanical pump to pump the sputtering chamber to the resistance unit 3.0×E 0 After the vacuum reaches Pa, turn on the molecular pump and use the molecular pump until the molecular pump reading reaches 450L / s;
[0048] S3, filling the sputtering chamber with argon gas, the flow rate of argon gas is 30 sccm, and the gas pressure is 1.0 Pa;
[0049] S4, respectively connect three DC power supplies to the three targets (one DC power supply for each target), set the sputtering power of the Ti target and the CuNb target to 100 W, the sputtering power of the CoCrFeNi target to 150 W, and the substrate bias voltage to -80 V;
[0050] S5. Sputtering the inner ring working surface of the precision spherical plain bearing 42CrMo steel and the surface of the single-polished silicon wafer:
[0051] ①. Keep the sample stage rotating during the sputtering process. First, ensure that the target baffle and sample baffle are not opened, and pre-sputter the three targets for 10 minutes each. Then open the baffles of the three targets of Ti, CuNb and CoCrFeNi and perform three-target co-sputtering for 15 minutes to obtain a layer of film.
[0052] ②. Turn off the CoCrFeNi target, and co-sputter the TiCuNb layer with the Ti and CuNb targets for 15 minutes to obtain another film;
[0053] ③, the above steps ① and ② are cycled for 4 more times to obtain 8 layers of film;
[0054] ④. Finally, Ti, CuNb, and CoCrFeNi targets were co-sputtered for 15 minutes to form the last layer of high entropy film. A total of 11 layers of high-temperature wear-resistant film materials were prepared on the surfaces of the two substrates, respectively, which were recorded as CoCrFeNi / Ti / CuNb multilayer materials.
[0055] S6. After sputtering, the target baffle is closed, the power supply and the argon valve are turned off, and the sample is taken out. The elements in each layer of the deposited CoCrFeNi / Ti / CuNb multilayer material are evenly distributed. The friction curve of the CoCrFeNi / Ti / CuNb multilayer material obtained in the high temperature wear test is stable, and the average friction coefficient is 0.28 (such as Figure 4 as shown).
[0056] Comparative Test 1: The difference between this test and Test 1 is that the baffle of the CuNb target is always closed in S5, and the other operations are the same as in Test 1. Finally, a CoCrFeNi / Ti multilayer material is obtained, and the average friction coefficient is 0.557.
[0057] Comparative experiment 2: The difference between this experiment and experiment 1 is that three target materials are always co-sputtered in S5 for a total of 2 hours and 45 minutes. Other operations are the same as in experiment 1. Finally, a CoCrFeNi / Ti / CuNb single-layer material is obtained with an average friction coefficient of 0.494.
[0058] By comparing the above three coatings, it can be seen that the CoCrFeNi / Ti / CuNb multilayer material prepared in Experiment 1 has better high-temperature wear resistance than the CoCrFeNi / Ti / CuNb single-layer material and the CoCrFeNi / Ti multilayer material. At the same time, it is found that the friction coefficient of the CoCrFeNi / Ti / CuNb multilayer material fluctuates less (see Figure 4 Curve 3 in the figure), which is related to the fact that the friction pair continuously acts on the amorphous and nanocrystalline coating of the CoCrFeNi / Ti / CuNb multilayer material during the friction process. The hard nanocrystalline layer and the soft amorphous layer work together to improve the wear resistance of the coating and reduce the fluctuation of the friction curve.
[0059] The CoCrFeNi / Ti / CuNb multilayer material prepared in Experiment 1 includes 5 TiCuNb layers and 6 CoCrFeNiTiCuNb layers, a total of 11 layers. Cu is a self-lubricating element that easily forms a self-lubricating structure of copper oxide (CuO) or cuprous oxide (Cu2O) layers, and easily forms a lubricating phase with excellent wear resistance with elements such as Ni and Ti, reducing severe adhesion during friction; Nb is a high-temperature resistant element that easily forms stable metal compounds with metal elements such as CoCrFeNiTi, significantly improving high-temperature performance, and obtaining a high-temperature wear-resistant multilayer material for the surface of precision parts, which can effectively protect mechanical equipment parts in extreme environments and increase their service life.
[0060] Figure 1 Schematic diagram of the CoCrFeNi / Ti / CuNb multilayer material prepared in Experiment 1. The CoCrFeNi / Ti / CuNb multilayer material includes 5 TiCuNb layers and 6 CoCrFeNiTiCuNb layers, for a total of 11 layers.
[0061] Figure 2 SEM image of the CoCrFeNi / Ti / CuNb multilayer material prepared for experiment 1, with the precision spherical plain bearing 42CrMo steel underneath layer 1.
[0062] Figure 3 This is a real photo of the precision spherical plain bearing 42CrMo steel used in Experiment 1. Location 1 is the working surface of the inner ring of the precision spherical plain bearing, and location 2 is the outer ring of the precision spherical plain bearing. The purpose is to prepare a high-temperature, wear-resistant multilayer material on the surface of location 1.
[0063] The tribological test was carried out on a standard friction and wear test equipment (model: MPT-3G). The pin-disk friction pair was loaded on the equivalent plane of the spherical bearing. The bearing was fixed and the pin-disk friction pair rotated. The high-temperature tribological performance test was carried out on three coatings prepared on the surface of single-polished silicon wafers. The following results were obtained: Figure 4The tribological curve comparison results shown are as follows: Curve 1 is the CoCrFeNi / Ti multilayer material prepared in comparative test 1, Curve 2 is the CoCrFeNi / Ti / CuNb single-layer material prepared in comparative test 2, and Curve 3 is the CoCrFeNi / Ti / CuNb multilayer material prepared in test 1. The average value of the tribological coefficient of the CoCrFeNi / Ti / CuNb multilayer material prepared in test 1 is 0.281, the average value of the tribological coefficient of the CoCrFeNi / Ti / CuNb single-layer material prepared in comparative test 2 is 0.494, and the average value of the tribological coefficient of the CoCrFeNi / Ti multilayer material prepared in comparative test 1 is 0.557. The friction coefficient of the CoCrFeNi / Ti / CuNb multilayer material prepared in test 1 is significantly reduced, and the high-temperature wear resistance is greatly improved.
Claims
1. A method for preparing a high-temperature wear-resistant multilayer material on the surface of a precision part, characterized in that The preparation method of high temperature wear-resistant multilayer material on the surface of precision parts is carried out according to the following steps: S1. Grind, polish and ultrasonically clean the working surface of the precision parts in turn to remove impurities, and then fix the precision parts on the motor shaft of the sample stage so that the two can rotate coaxially; S2, respectively installing the sample stage, Ti target, CuNb target and CoCrFeNi target in S1 in the sputtering chamber, and then evacuating the sputtering chamber; S3, filling the sputtering chamber with argon gas; S4, connecting three power supplies to the three targets respectively, adjusting the bias voltage and the sputtering power of the Ti target, the CuNb target and the CoCrFeNi target; S5. Sputtering the working surface of precision parts: ①. During the sputtering process, the sample stage is kept rotating, and the baffles of the three targets of Ti, CuNb and CoCrFeNi are kept open for three-target co-sputtering for 15min to 20min; ②. Turn off the CoCrFeNi target, and co-sputter the TiCuNb layer with the Ti and CuNb targets for 15min to 20min; ③, repeat the above steps ① and ② 4 times in sequence; ④. Finally, Ti, CuNb, and CoCrFeNi targets were co-sputtered for 15 to 20 minutes to form the last layer of high entropy film. A total of 11 layers of high-temperature wear-resistant multilayer materials were prepared on the working surface of the precision parts, which were recorded as CoCrFeNi / Ti / CuNb multilayer materials. S6. After sputtering, close the target baffle, turn off the power supply and argon valve, and take out the sample.
2. The method for preparing a high temperature wear-resistant multilayer material for the surface of a precision part according to claim 1, characterized in that The precision parts described in S1 are shaft-type structures.
3. The method for preparing a high temperature wear-resistant multilayer material for the surface of a precision part according to claim 2, characterized in that The shaft structure described in S1 is a spherical bearing, a gear or a lead screw.
4. The method for preparing a high temperature wear-resistant multilayer material for the surface of a precision part according to claim 1, characterized in that The ultrasonic cleaning described in S1 is ultrasonic cleaning in anhydrous ethanol for 5 min to 10 min, with an ultrasonic frequency of 60 Hz to 90 Hz, followed by drying with cold air.
5. The method for preparing a high temperature wear-resistant multilayer material for the surface of a precision part according to claim 1, characterized in that The flow rate of the argon gas described in S3 is 30 sccm to 50 sccm.
6. The method for preparing a high temperature wear-resistant multilayer material for the surface of a precision part according to claim 1, characterized in that The three power supplies described in S4 are all DC power supplies.
7. The method for preparing a high temperature wear-resistant multilayer material for the surface of a precision part according to claim 6, characterized in that In S4, the power is adjusted to 100 W for the sputtering power of the Ti target and the CuNb target, 150 W for the sputtering power of the CoCrFeNi target, and the bias voltage is -80V.
Citation Information
Patent Citations
Sputtering method
JP2004232045A
Method of producing a wear-resistant nanostructured coating
RU2742751C1